INDONESIAN GENERATION Z'S IMPACT ON DEMOCRACY AND LEGAL DYNAMICS IN INDONESIA - Rafael Gonzales Sibarani; Mazidatul 'Inayati Al Yasiri; Shifa Salsa Sabilah; Devinda Syahrani (Problematika Hukum, 2022)
Indonesia's population is made up of 27.94% members of Generation Z, which comprises those born between 1997 and 2012, according to a 2020 Central Statistics Agency (BPS) poll. Considering that this generation grew up with the rise of social media and technology, there are serious concerns about how involved they are in democracy and the judicial system. This article highlights the critical role that Generation Z is playing in developing a new paradigm for a more responsive legal system and dynamic democracy, especially through social media, which they have grown to rely on. With their technological prowess, Generation Z makes use of social media platforms as tools to voice political views, mobilize collective action, and disseminate up-to-date information. Their activism enriches democratic dialogue, creating space for more inclusive voices. Social media is also a channel for building legal awareness, with discussions on regulations and human rights. In conclusion, the basis for constructive change is laid by Generation Z's involvement in democracy and their interaction with the legal system via social media. They are using technology to alter Indonesia's political and judicial processes, as well as to create lively forums for discussion.Keywords: Generation Z; Democracy and Legal System; Social Media.